2016
DOI: 10.1021/acs.jpcc.6b04478
|View full text |Cite
|
Sign up to set email alerts
|

Nanodomains Coupled to Ferroelectric Domains Induced by Lattice Distortion in Self-Doped LuMnxO3±δ Hexagonal Ceramics

Abstract: Self-doped h-LuMn x O3±δ multiferroic ceramics with 0.92 ≤ x ≤ 1.12 were studied for the dependence of magnetic properties on x. Interlocking of lattice distortion at the nanoscale with ferroelectric (FE) domains in bulk RMnO3 materials is mostly unknown. Here we report occurrence of nanodomains in transmission electron microscopy (TEM) images with the presence of antiphase boundaries/ferroelectric domain walls separating nano-FE domains. Observed chemical inhomogeneity across the crystalline grains of the cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
(123 reference statements)
0
8
0
Order By: Relevance
“…The results for the L 3 /L 2 ratio of h-LuMn x O 3± samples with 1 day annealing are from Figure S3(b) of ref. [25]. Although the nature of covalent bonding may result in slight changes of the valence state the present analysis in Figure 4(b) exhibits a rather constant value of the Mn 3+ oxidation state for all measurements, or very close to it [26][27][28][29].…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…The results for the L 3 /L 2 ratio of h-LuMn x O 3± samples with 1 day annealing are from Figure S3(b) of ref. [25]. Although the nature of covalent bonding may result in slight changes of the valence state the present analysis in Figure 4(b) exhibits a rather constant value of the Mn 3+ oxidation state for all measurements, or very close to it [26][27][28][29].…”
Section: Resultsmentioning
confidence: 48%
“…Although most attention was devoted on exploring the properties of the 6-fold vortices in this family of multiferroic oxides, there are images of topology breaking of 6-fold vortices or structurally distorted cores [31][32][33][34]. The broad microscopy analysis of the FE domains in ceramics of the current study disclosed frequent topology breaking of the 6-fold vortices, also the interaction of the FE polarization and partial edge dislocations and stacking faults in the lattices, of which the effect on the magnetic properties requires more experiments and theoretical calculations via DFT approaches [25].…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Plate-like single crystals of ErMnO 3 cooled through T C under applied loads revealed conversion of isotropic distribution of vortices to lengthy stretched stripes linking vortices to antivortices that moved far apart along easy slip directions dragged by forces coming from the intense shear strain gradients of high temperature plasticity . Minute shifts of chemical composition are expected in solid state reacted samples, and it was already shown that planar defects and dislocations can be found in ceramics of this study, but they appeared mostly at submicron scales. , One must assume that wavy stripe-like FE patterns in Figure a from annealing the x = 0.94 sample at 1510 °C is evidence that this temperature stays below the corresponding T C of the material. Observed features are intrinsic and did not originate from mechanical stress/strain fields or fluctuating chemical composition.…”
Section: Resultsmentioning
confidence: 49%
“…Thus, to better understand and further enhance ferroelectric responses, domain evolution during heating and cooling cycles must be studied. For illustrating domain structure and distribution, many techniques have been employed including transmission electron microscopy (TEM), optical microscopy (OM), , backscattered mode scanning electron microscopy (BM-SEM), ,, and piezoresponse force microscopy (PFM). ,,, The skillful in situ combination with Raman spectra or Raman mapping will make the discussion between domains and crystal structures more fascinating. , …”
Section: Introductionmentioning
confidence: 99%